Bilateral asymmetry of the humerus in Neandertals, Australian aborigines and medieval humans. Issue 1 (22nd May 2018) - Kubicka, Anna Maria; Nowaczewska, Wioletta; Balzeau, Antoine; Piontek, Janusz
Abstract: Objectives: Bilateral asymmetry of diaphyseal shape and size may be a reflection of relative activity levels and patterns of habitual biomechanical stress in the upper arms of Neandertals and Homo sapiens . The main purpose of our study was to assess the level of directional asymmetry of humeral cross sections in Neandertals, recent Australian aborigines, and medieval farmers. Materials and Methods: Indices of directional and absolute asymmetry (%DA and %AA) of humeral cross‐sectional properties in Neandertals and recent Homo sapiens were calculated. Evenly distributed semilandmarks around the external and internal borders of cortical bone were digitized in the course of computed tomography for analysis of shape differences between sides of the body. Results: The medieval farmers were characterized by significant %DA and %AA for polar second moment of area ( J ), ratio of maximum to minimum second moments of area, and ratio of antero‐posterior to medio‐lateral bending strength. In Australian aborigines, only J in males shows significant %DA and %AA, while Neandertals exhibit no significant asymmetry of any cross‐sectional properties. Differences in cross‐sectional shape between sides of the body were established in all three analyzed groups. Discussion: High levels of directional asymmetry of cross‐sectional shape and properties in medieval farmers may be caused by the performance of more physically demanding tasks using one side of the body from an early age in that population. Various patterns of asymmetry in Neandertals and modern humans may be caused by different habitual behaviors during growth, eco‐geographic patterns in body proportions, genetic factors, and differences in ontogeny.